Pemanfaatan Model Pembelajaran TGT dalam Meningkatkan Keaktifan Siswa pada Mata Pelajaran SKI di Madrasah Ibtidaiyah - Alayk Hikam Badruttamam; Dinar Ramadhani; Putri Nurul Aini; Septiana Ramadhani; Bunga Aulia Azzahra; Widia Sinta Wati; Safa Sabina; Dian Rif'iyati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by the view that the subject of Islamic Cultural History (SKI) has received limited attention, as most of the material is delivered in a narrative manner that tends to be monotonous. Although lectures remain a relevant method for SKI, alternative approaches are needed to enhance student engagement and reduce boredom. The purpose of this research is to describe the condition of SKI learning, explain the implementation of the cooperative learning model Teams Games Tournament (TGT), and analyze its implications for student activeness in the learning process. This study employs a qualitative approach with a library research method, examining various sources such as books, scientific journals, and previous relevant studies. Data collection techniques were carried out through documentation, while data analysis used descriptive qualitative analysis. The findings indicate that the application of the TGT model can increase student activeness through group work, games, and tournaments that encourage active participation. Furthermore, the TGT model creates a more interactive and enjoyable learning atmosphere, which positively impacts students’ understanding and learning outcomes. Thus, the TGT learning model can serve as an effective alternative for improving the quality of SKI learning in Madrasah Ibtidaiyah.